Cost of illness from occupational hand eczema in Germany. (22nd July 2013) - Diepgen, Thomas L.; Scheidt, Reginald; Weisshaar, Elke; John, Swen M.; Hieke, Klaus
Summary Background There is little knowledge about the costs of occupational hand eczema. Objectives To estimate the societal costs of patients with occupational hand eczema in Germany. Methods Resource use during the past year, disease severity and quality of life [Dermatology Life Quality Index (DLQI)] were gathered for patients with occupational hand eczema before they entered a special rehabilitation programme. Costs were calculated from the societal perspective. The analysis focused on all patients and the severity groups no signs/mild (group A) and moderate to severe (group B). Results One hundred and fifty‐one patients were analysed, with a mean age of 44.9~years and a mean DLQI score of 10.9; 64.9% were male. Sickness absence was recorded for 62.9% of all patients (76.4~days on average in the last 12~months). Annual societal costs were €8799 per patient. Indirect costs represented 70% of total costs. Quality of life (DLQI) was statistically different across both severity groups (group A, 7.9; group B, 12.9), but direct treatment costs were not (€2705 versus €2610, respectively). There was a trend towards higher indirect costs in patients in severity group B (group A, €5120; group B, €6796). Conclusion The annual societal costs of patients with occupational hand eczema in this study are high, and similar to those for severe psoriasis and atopic dermatitis.